Vegetables and fruits : nutritional and therapeutic values - Li, Thomas S. C. (CRC Press, 2008)
Features information on therapeutic and nutritional values for more than 200 species of fruits and vegetables. This work presents flavonoid, isoflavone, and carotenoid content in raw vegetables as well as human nutritional values including protein, vitamins, and minerals. It provides nutritional information for countering and preventing disease.